Pengaruh Motivasi Kerja dan Beban Kerja terhadap Kinerja Karyawan di CV Brother Online Stationery - Mita Ferdianti; Iwan Asmadi; Bambang Haryono (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the effect of work motivation and workload on employee performance at CV Brother Online Stationery. The sampling method used in this study was saturated sampling, where the total population consisted of all 34 employees of CV Brother Online Stationery. The data analysis method employed multiple linear regression tests. Partial hypothesis testing using the t-test indicates that work motivation and workload have a positive and significant effect on employee performance. This is evident from the results of the t-test on the work motivation variable, where the calculated t-value (3.106) is greater than the table t-value (1.695), with a significance value of 0.004, which is less than 0.05. Similarly, for the workload variable, the calculated t-value (3.140) is greater than the table t-value (1.695), with a significance value of 0.004, which is less than 0.05. In addition, simultaneous hypothesis testing indicates that work motivation and workload collectively influence employee performance at CV Brother Online Stationery. The results of the f-test (simultaneous test) show that the calculated f-value (11.613) is greater than the table f-value (3.30), with a significance value of 0.000, which is less than 0.05.